Are Indian Adolescent Girl Students More Conscious About Their Body Image Than Their Colleague Boys? - Hasmukh D Shah; Wasim A Shaikh; S K Singh (Medsci Publications, 2012)
Background: Body weight plays a main role for the Indian adolescent college students for their physical look. Body mass index reflects health status of individual. Body mass index is associated with self esteem of students. Methodology: A cross section study was conducted on 96 students of 17-19 years of age group. Nutritional status of participants was assessed by Omron HBF-362 body fat analyzer. The body weight, body mass index, resting metabolism, metabolic age, body fat percentage and visceral fat were assessed by this instrument. Dietary questionnaire was taken from the students. Results: Body mass index (P < 0.01), resting metabolism (P < 0.0001) and visceral fat (P < 0.0001) of Indian adolescent girls were found to be significantly lower than their collegue boys. Girls are not satisfied with their body image and Indian adolescent girls are skipping their meal rather than doing physical exercise. Conclusion: We may conclude that nutritional status and awareness about nutrition play a main role for individual's body image.